The Economics of Protected Marine Species: Concepts in Research and Management - Kristy Wallmo (Frontiers Research Topics, 2016)
Protected marine species have populations that are depleted, decreasing, or are at-risk of extinction or local extirpation. As of 2015 The International Union for the Conservation of Nature, a global environmental organization, lists approximately 737 marine species worldwide that are considered at risk of extinction. Many are provided legal protection through national laws requiring research and management measures aimed at recovering and maintaining the species at a sustainable population level. Integral to the policy decision process involving the management and recovery of marine species is the consideration of trade-offs between the economic and ecological costs and benefits of protection. This suggests that economics, at its core the study of trade-offs, has a significant role.